Economic Evaluation of Self-Administered Dual-Task Training Reducing Falls in Community-Dwelling Older Adults: Cost-Effectiveness Analysis of a Multicenter Randomized Control Trial - Mohammad Jobair Khan; Kenneth N. K. Fong; Thomson Wai-Lung Wong; William Wai-nam Tsang; Wai-chi Chan; Cynthia Chen; Stanley John Winser (Journal of Physical Activity and Health, 2026)
Background : Uncertainty exists among health practitioners and policymakers regarding the adoption of cost-effective interventions to prevent falls in community-dwelling older adults. This study compares cost-effectiveness of self-administered dual-task training (sDT) with self-administered single-task training (sST) for fall prevention. Methods : This prospective randomized controlled trial included 216 older adults aged over 65 years with a previous fall history. Assessments were conducted at baseline, postintervention, and a 6-month follow-up, and the study outcomes were measured using fall frequency and quality of life. The association between treatments and prospective fall-related direct medical costs was assessed using 2-part models. A half-cycle corrected Markov model estimated cost-effectiveness over 10 years and calculated incremental cost-effectiveness ratios and quality-adjusted life years. The strength of the findings was evaluated using deterministic and probabilistic sensitivity analyses. Results : Participants of the sDT group had significantly lower hospitalization costs (mean = US$34, coefficient [coef.] = −169,262; 95% confidence interval, −173,614.7 to −164,910; P < .0001), compared with the sST group (mean = $211.31; coef. = 24,724.36). Compared with sST, sDT meets the highly cost-effective healthcare approach criterion with an incremental cost-effectiveness ratio of −$737,347. Base-case analysis reported the cost (sDT = $1995, sST = $2692; difference: −$696) saving of sDT interventions and improvement in quality-adjusted life years (sDT = 8.67, sST = 8.39; difference: −0.29) due to practicing sDT with a health benefit of 0.09 quality-adjusted life years per person per year. Conclusion : Findings of this cost-effective analysis suggest that sDT improves quality of life for participants and reduces healthcare costs due to a lower fall incidence and hospitalization, meeting the cost-effective threshold criteria from a Hong Kong healthcare perspective.